Epithelioid Sarcoma of the Penis: A Case Report. (22nd May 2012) - Colombo, Fulvio; Franceschelli, Alessandro; Schiavina, Riccardo; Gentile, Giorgio; Passaretti, Giovanni; Martorana, Giuseppe
ABSTRACT: Introduction. Epithelioid sarcoma of the penis is a slowly growing soft tissue neoplasm that rarely arises from the penis. Aim. The aim of this case is to describe this rare pathology and to underline the importance of differential diagnosis with benign diseases such as Peyronie's disease. Method. We report the case of a 20‐year‐old man who referred the onset of a progressive left dorsolateral penile curvature (about 60°) started 3 years before. The patient was evaluated with two US examinations that revealed two sites of tunical thickening with normal hemodynamic evaluation. The physical examination demonstrated a dorsal fibrotic plaque of about 2.5 cm. Results. A juvenile form of Peyronie's Disease was diagnosed, and the patient was scheduled for surgical treatment (plaque's incision/excision and grafting). Intraoperative appearance showed that the great part of the left cavernous body was substituted by a very tough tissue which deeply involved the erectile tissue; intraoperative frozen section was suspicious for mesenchymal epithelioid neoplasm. In order to obtain definitive histological analysis and collect proper informed consent, we preferred to proceed with our original project, applying a dual graft (buccal mucosa and allograft dermal matrix) to cover the wide excised area. The final histological report confirmed the diagnosis of epithelioid sarcoma. Postoperative CT and MRI, at 3 and 6 months from surgery, were negative for metastases. The patient underwent radical intervention after 6 months. Conclusions. Epithelioid sarcoma of the penis and Peyronie's Disease can present with similar clinical findings although they obviously entail a different clinical progress. Since the diagnosis of neoplasm can be established only by the pathologist on biopsy specimen, in cases of unusual clinical presentation of Peyronie's disease (especially in young men suffering from a fast‐growing penile induration), an early histological assessment should be performed to avoid the possibility of misdiagnosis in case of this poor‐prognosis disease and to assure the definitive diagnosis.Colombo F, Franceschelli A, Schiavina R, Gentile G, Passaretti G, and Martorana G. Epithelioid sarcoma of the penis: A case report. J Sex Med 2013;10:2871–2874.